NCOG-11. POST-RADIOSURGICAL OUTCOMES OF CYSTIC VESTIBULAR SCHWANNOMAS, A SYSTEMATIC REVIEW AND META-ANALYSIS. (9th November 2020) - Hamidi, Nima; Massaad, Elie; Goetz, Jacalynn; Mansouri, Alireza
Abstract: INTRODUCTION: Vestibular schwannomas (VS) are benign neoplasms that present as cystic or solid variants. Cystic VS are associated with fast and unpredictable growth patterns, and their adherence to nearby structures can lead to poor surgical outcomes. While radiosurgery (RS) has gained popularity for VS, the heterogeneity of literature necessitates a systematic review. METHODS: Following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA), PubMed, EMBASE, Web of Science, and Cochrane were searched for observational studies reporting cystic and solid VS radiosurgical outcomes. Pooled estimates were calculated using random-effect models with generic inverse variance to compare tumor control rates between cystic and solid VS. Quality assessment was done using the Newcastle Ottawa Criteria (NOS). RESULTS: The search yielded 2, 989 studies from which 680 were selected for full-text screening and 6 were included in this review and meta-analysis. The quality of studies ranged between good (3 studies, NOS 7/9), fair (2 studies, NOS 6/9), and poor (1 study, NOS 4/9). The patient pool included 1, 070 solid and 347 cystic VS, all treated by gamma knife RS. No difference in tumor control was observed (RR: 1.02, 95%CI 0.91-1.16, p=0.7). 3 studies reported post-RS complications. Haseguawa reported hydrocephalus in 7 of 74 cystic cases. Ryu reported 1 case of hydrocephalus and 1 case of trigeminal pain in their 14 cystic cases. Shirato reported 5 transient trigeminal Neuralgia, 1 transient vertigo and 1 shunt operation in their 20 cystic cases. CONCLUSION: Evidence presented in this meta-analysis supports the safety and efficacy of radiosurgery in treating cystic VS.